Maarten Prak’s Citizens without Nations and the Legal History of Spain - Herzog, Tamar (TSEG - The Low Countries Journal of Social and Economic History, 2020)
This text summarizes some of the findings regarding municipal citizenship (vecindad) and membership in the kingdom community (naturaleza) in Spain from the middle ages to the twentieth century and compares and contrasts them with the conclusions reached by Maarten Prak. Basically agreeing with his main discoveries, it nonetheless argues that in Spain, at least, many of the features described by Prak did not disappear in the aftermaths of the French Revolution but instead persisted into the nineteenth and the twentieth century. Furthermore, this text also advocates for the importance of law. It suggests that bringing in the law would have facilitated both the description and the understanding of many of the very interesting phenomenon described by the author.